Research assistant as partner: Collective leadership to facilitate co-production - Hill, Joshua Timothy; Thomas, Christy; Brown, Barbara (International Journal for Students as Partners, 2019)
In this article, we chronicle our experience of student-faculty partnership within a Scholarship of Teaching and Learning design-based research study. We present our experience of partnership in relation to the student-faculty partnership, collective leadership, adult learning and knowledge building literatures. Key characteristics of our student-faculty partnership are recognizingand using intellectual and experiential resources; practicing principles of knowledge building; and differentiating top-down and lateral decision making. We find the affordances of our partnership to be increased productivity, learning from each other and diversity of ideas and perspectives and limitations to be substantial time commitment, underlying beliefs about students’ capabilities and student-faculty ratio to limitations. We conclude by exploring the impact of our partnership on students, faculty and the university.